2016
DOI: 10.1111/cmi.12681
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptome analysis ofAspergillus fumigatusexposed to osmotic stress reveals regulators of osmotic and cell wall stresses that are SakAHOG1and MpkC dependent

Abstract: Invasive aspergillosis is predominantly caused by Aspergillus fumigatus, and adaptations to stresses experienced within the human host are a prerequisite for the survival and virulence strategies of the pathogen. The central signal transduction pathway operating during hyperosmotic stress is the high osmolarity glycerol mitogen-activated protein kinase cascade. A. fumigatus MpkC and SakA, orthologues of the Saccharomyces cerevisiae Hog1p, constitute the primary regulator of the hyperosmotic stress response. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 77 publications
(149 reference statements)
8
60
0
Order By: Relevance
“…To test the former hypothesis, we investigated if constitutive expression of the A. fumigatus bZIP transcription factor encoding gene atfA , that is known for its involvement in spore maturation and spore ROI defense (Hagiwara et al, 2009; Hagiwara et al, 2014; Hagiwara et al, 2016), could restore the Δ aceA survival defect in macrophages (Figure 5B). As previously reported (Pereira Silva et al, 2016), we observed a significant loss of survival in activated BMDMs challenged with an Δ atfA mutant compared to the wild type that was similar to the Δ aceA strain (Figure 5B). Forced expression of atfA brought survival back to wild-type levels in a Δ aceA background (Figure 5B) despite its poor growth phenotype when grown on solidified media (Figure S5A).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…To test the former hypothesis, we investigated if constitutive expression of the A. fumigatus bZIP transcription factor encoding gene atfA , that is known for its involvement in spore maturation and spore ROI defense (Hagiwara et al, 2009; Hagiwara et al, 2014; Hagiwara et al, 2016), could restore the Δ aceA survival defect in macrophages (Figure 5B). As previously reported (Pereira Silva et al, 2016), we observed a significant loss of survival in activated BMDMs challenged with an Δ atfA mutant compared to the wild type that was similar to the Δ aceA strain (Figure 5B). Forced expression of atfA brought survival back to wild-type levels in a Δ aceA background (Figure 5B) despite its poor growth phenotype when grown on solidified media (Figure S5A).…”
Section: Resultssupporting
confidence: 89%
“…Constitutive expression of either crpA or the transcription factor atfA , shown to govern spore ROI detoxification mechanisms (Hagiwara et al, 2009; Hagiwara et al, 2014; Hagiwara et al, 2016; Pereira Silva et al, 2016), rescued survival of the Δ aceA mutant in confrontations with macrophages (Figure 5) and supports the view that copper mobilized by host cells partially exerts its lethality by potentiating host ROI toxicity. In S. cerevisiae, similar transcriptional control of SOD1 by Ace1p was observed (Gralla et al, 1991).…”
Section: Discussionsupporting
confidence: 63%
“…Meanwhile, some members of this gene group, for example, nikA , ypdA , tcsA , and tcsB , are important upstream elements of the HogA/SakA signaling pathway in A. nidulans , which regulates oxidative stress response via AtfA itself [73, 74]. In their most recent publication, Silva et al [31] found that MpkC and SakA, which regulate the expressions of atfA and atfB , also influence the transcriptions of “two-component signal transduction system” genes, which are important for their own activation in A. fumigatus . The most “two-component signal transduction system” genes (7 genes) were upregulated under MSB stress suggesting that this positive feedback regulation is particularly important under this type of oxidative stress (Table 2, Supplementary Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…AtfB, an orthologue/paralogue of AtfA, is an important transcription factor which integrates mycotoxin production and oxidative stress response in Aspergillus parasiticus and probably in other aspergilli as well [30]. Most recently, the involvement of the bZIP-type transcription factors AtfA-D in the orchestration of stress responses mounted against various types of environmental stress was also demonstrated in A. fumigatus [31]. AtfA also influences asexual and/or sexual development in Neurospora crassa , A. nidulans , and F. graminearum [12, 24, 25, 32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation